Co-designed solutions for collecting food & nutrition security data with mobile devices: What worked (and did not) from a NGO, government and research partnership - Chesterman, Sabrina; Lamanna, Christine; Hammond, James; Namoi, Nictor; Wakelin, Oliver; Ng'endo, Mary; Wijk, Mark T. van; Rosenstock, Todd S. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2017)
The extent and implications of under nutrition in Sub-Saharan Africa have catalyzed political action and programs on the ground. For example, the United Nations has declared a decade of action (2016-2026) and the Sustainable Development Goals have set ambitious targets to end hunger and undernutrition by 2030. Countries and development partners are moving too, individually and in coordinated actions through programs such as Scaling Up Nutrition (SUN).